Experiences of Children Living in Overcrowded Homes: A Case of Ghana - Adu Henaku, Eugene (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The study explored children's experiences living in overcrowded homes in Apewosika Community, a suburb of the Cape Coast Metropolis in the Central Region of Ghana. The descriptive phenomenological research design was adopted for the study. A face-to-face interview was used to collect data from 10 participants aged 12-17 years. These participants were purposively sampled from 10 nuclear families based on the inclusion criteria. The thematic data analysis method was used in analysing the data collected. The themes that emerged from the data analysis are lack of privacy, sleep disturbance, difficulty studying at home, and the spread of diseases. The study concludes that enough space should be provided at home for children to have rooms to reduce the spread of infectious diseases among children and their family members, promote sleep, ensure their privacy and promote their studies at home. Keywords: Children, Ghana, Housing, Overcrowded Homes